Effect of Pruning and Application of Plant Growth Promoting Rhizobacteria on Anthracnose Disease and Yield of Red Chili - Ghilman Ainnudin; Eny Fuskhah; A’isyah Surya Bintang (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2025)
Red chili (Capsicum annuum L.) is a widely consumed, high-value horticultural crop in Indonesia, but its national productivity remains low at 9.59 tons.ha-1, far below its potential due to factors such as disease, limited land, poor soil fertility, and suboptimal cultivation, highlighting the need for improved farming practices. Pruning can be implemented to promote branching and direct photosynthate to productive parts of the plant. The application of Plant Growth Promoting Rhizobacteria (PGPR) also presents a promising solution, as these microbes enhance nutrient uptake efficiency, stimulate plant growth through hormone production, and suppress pathogens such as the anthracnose-causing agent through antagonistic mechanisms and induced systemic resistance (ISR). Based on the research results, the combination of apical+water shoot pruning (P3) with the application of PGPR at 27.5 ml.L-1 (B3) significantly enhanced vegetative growth (plant height, number of leaves), accelerated flowering (39 days after planting), and increased fruit production (15 fruits per plant; 247.7 g per plant) in red chili variety HPT 1730, although the results remained below genetic potential due to environmental factors and anthracnose infection. The PGPR 27.5 ml.L-1 treatment also increased phenol content (3.10 mg.g-1) and stomatal opening (71.30%), but was not yet effective in significantly suppressing anthracnose incidence.